A study on the relationship between consumer price index, interest rates, money supply and exchange rate towards property index in Malaysia / Azim Izzuddin Muhamad - Muhamad, Azim Izzuddin (2007)
The purpose of this paper is to determine whether the relationship between consumer price index (CPI), interest rate refer to base lending rate (BLR), money supply (M2) and exchange rate (YEN/RM) can affect significantly towards property index (PI) in Malaysia. With that, CPI, interest rate, money supply and exchange rate will be as independent variable and PI will be as dependent variable. The study of data has been recorded in 10 years from 1996 to 2005 in monthly basis. Multiple Linear Regression analysis is used in finding out the relationship between dependent and independent variables. Based on the analysis, there is a significant relationship between interest rate (BLR) with the PI. However, there is no significant relationship between CPI, money supply and exchange rate with the PI. The PI reacts positively with the changes in interest rate but reacts negatively towards the changes in CPI, money supply and exchange rate.